Contribuições da pesquisa colaborativa na prática pedagógica docente, utilizando a aprendizagem de projetos como estratégia de ensino - Ilha, Phillip Vilanova (2016)
This thesis was developed at a state school in the city of Santa Maria/RS and aimed to analyze as the collaborative research interferes in the pedagogical practice of teaching, through project learning as a teaching strategy. The work stood at in the framework of collaborative research, with exploratory objective and characterized with regard to the procedures, such as collaborative research. The methodological course, lasting three years, was built in the course of the study and the results were presented in the form of two articles and a manuscript. The first article analyzes the process and the impact of collaborative interventions applied at school in the first year of the study. The results of this phase have shown that the collaborative research has developed conceptual and motivational changes in teachers and these have demonstrated difficulties in modifying their teaching practices because they are too tied to pedagogical routines required by the education system. The second article was characterized by research into the perceptions of teachers and students on a proposal for learning by project applied to three classes of the seventh year of primary school, with different methodological approaches (learning projects and projects teaching). It was found that teachers and students perceived greater motivation and learning when developed learning projects in which students were able to build their knowledge collaboratively and the teacher has had the role of learning mediator and, in educational projects, where there was a centrality of the process by the teacher, the perception of learning and motivation were lower. In the manuscript, was investigated contributions in the teaching practice of a proposal for learning project, mediated by collaborative research, applied in the second and third year of the research. The results of this period have exposed that in the second year of the study, teachers showed a transition from traditional teaching to teaching by projects, exceeding the linearity of programmatic content and disciplinary education to multidisciplinary teaching and the following year, solidified pedagogical actions through learning active student, seeking a critical and contextualized perspective of content as well, unveiled the passage of disciplinary and multidisciplinary teaching for interdisciplinary teaching. Overall, collaborative research brought about changes in the pedagogical teaching actions throughout the study and when teachers build their concepts and ideas and were experiencing a positive pedagogical practices have become able to analyze and change their teaching activities in the classroom. Finally, we conclude that collaborative research was important mechanism in the professional development of teachers in a demonstration that the shared reflexive action favors the processes of learning and professional development of teachers and, in the reframing process of teaching practices, learning by projects has proved as an important teaching strategy to exploit the potentialities of teaching transformation.